Identifying Land Degradation and its Driving Factors in the Aral Sea Basin From 1982 to 2015 - Berdimbetov, Timur; Ma, Zhu-Guo; Shelton, Sherly; Ilyas, Sana; Nietullaeva, Sahibjamal (Frontiers in Earth Science, 2021)
Land degradation is one of the greatest ecological issues in the Aral Sea Basin (ASB). This study focuses on investigating land degradation in ASB during 1982-2015 using the Normalized Difference Vegetation Index (NDVI) as a proxy. The residual trend (RESTREND) for temperature, precipitation, soil moisture adjusted NDVI has been applied to identify the land degradation in ASB and quantify the contribution of climate factors such as temperature and rainfall. In addition, a binary logistic regression model is adopted to assess the contributions of land transition, socio-economic, and topographical conditions on land degradation. Based on RESTREND, the relative contribution of precipitation (30.2%), soil moisture (23%), and temperature (11.4%) indicate that precipitation is one of the main driving climate factors for land degradation. The results further showed that 36.5% of ASB is degraded, which is mostly concentrated in the lower part of the ASB. In contrast, 33.2% of ASB depicts land improvement, especially in the upper part of the basin. According to the land transition assessment 66.6% of the water area and 11.68% of forest converted to barren land and shrubland during the study period. The binary logistic regression model revealed that the water and forest area transitions into shrubland and barren land are major contributor of contemporary land degradation in ASB. Cropland recorded a net increment by 2.69% of its initial area, and the abandoned cropland converted to shrubland and barren lands that negatively impacted land cover change. This in-depth analysis of land degradation can help in designing the policy interventions and implementing land restoration plans in the area.